Understanding 5G mobile networks : a multidisciplinary primer - Curwen, Peter; Whalley, Jason (Emerald Publishing Limited, 2021)
Most of the literature on 5G has been in the form of standards, reports, and industry papers and articles. Because of this, researchers from non-scientific or non-engineering disciplines have struggled to understand how it is or could be operationalized and standardized across the globe. Here Peter Curwen and Jason Whalley offer the first manageable overview of 5G for a non-technical audience. This book provides a full review of the current literature, both academic and professional; an in-depth but non-technical discussion of the historical background of the development of 5G; and a broad, multidisciplinary survey of major issues including spectrum, and the licensing and launch of 5G networks throughout the world, distinguishing standalone 5G from non-standalone 5G. Throughout, there is consideration given to how operators and equipment vendors make money from mobile networks, and where money is potentially to be made in the years to come. 'Understanding 5G Mobile Networks: A Multidisciplinary Primer' is a must-read not only for researchers and students in economics, business, strategy, and operations and logistics, but also for regulators, mobile companies, vertical operators, and anyone else interested in the development of this vital technology.